Optimization of Daily Warehouse Storage PT. XYZ with Shared Storage Method - Sofianty, Dian Maulidia; Hakim, Wafa Nurul; Indraswati, Haura Nailah; Zepanya, Fernando; Alawiyah, Tuty; Handayani, Melia; Tsani, Rubby Rahman (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
PT XYZ is a company engaged in ship repair and maintenance services and port management services. The problems faced by PT XYZ in carrying out its business lines are related to the effective and efficient operational managerial activities of raw material warehousing. Problem solving steps are carried out by testing data processing and analysis using the shared storage method as a solution step related to the problem of warehousing layout and optimization. Problem solving with the shared storage method is a method of reconditioning the warehousing layout with the principle of First in First out or fast moving where the layout of goods is classified based on the order of the flow of goods movement according to the operational needs of PT XYZ activities. Based on the calculation results, if the company applies the proposed layout, there is an average distance savings of 4 m2. The layout of the placement of raw materials based on the proposed improvements has a more organized condition and facilitates the flow of goods movement as well as inputting the flow of goods in and out which can be more efficient if the goods are organized and inputted administratively, this also affects the quality of goods.